Self-learning guide "Mathematics in questions and answers. Part 3" - Lapuzina, Olena Mykolayivna (Національний технічний університет "Харківський політехнічний інститут", 2021)
This methodic guide is designed for international students who study at the preparatory departments of Ukrainians universities. In this methodic guide students can find the basic theoretical questions and answers for the main topics to be covered during the Math educational course (2 semester). The special attention to the basic concepts of the Mathematics theory and scientific style in Mathematics are focused in the methodic guide. The methodic guide includes some basic problems of Sequences, Limits, Derivatives, Integrals and Geometry. Active learning style encouraged throughout, helping students really get to grip with the theory and getting them ready for successful mastery of higher Mathematics course. This methodic guide may be useful for international students of preparatory courses at universities, secondary schools, high schools and colleges. The book is also intended to be useful for Mathematics teachers who work with international students. Authors believe that this methodic guide should not just be a collection of mathematical facts carefully laid out, so the student can open it and cram in whatever formula they have to remember for tomorrow's exam. A Math methodic guide, especially for international students, should be full of questions, not just exercises. Questions that require some thought to answer. After all, "it's the questions that keep the students interested, not the answers." The basic issues of the theory give the possibility to address gaps in knowledge, acquire the knowledge needed for all major sections from the school Mathematics and revise the theory independently, without any other assistance.
Keywords: guide; mathematics; integrals; geometry; derivates; limits